The impact of destination and tourist behavioural attributes towards tourist loyalty in Jurusalem, Palestine: the mediating effect of political stability - Edais, Shehab Nafeth
Tourism industry plays a vital role in the economic development of any country by attracting foreign tourists resulting in positive country image. International tourism in Palestine has been economically and culturally undesirable because it has been subject to political turmoil over the past decades, and its tourist arrivals have not fully capitalized on the potential that the region holds. This is compounded by the negative image that the media has developed about Palestin concerning instability as opposed to actual reality in stability, security, safety and as such, it has become essential to disseminate the right image. The turbulent situation in Jerusalem occasioned by Israeli Palestinian crisis put euphoria in the mind set of tourist visiting the country . Therefore, this study is attempted to evaluate the role of various factors (destination image, tourist trust, and tourist emotion and perceived risk) under the mediation role of political stability towards tourist retention in Jerusalem. A quantitative methodology was applied in this research. The tudy has collected the primary data through questionnaire. The data were collected from 384 tourists who had visited Jerusalem by using cluster and non-probability purposive sampling technique. In the second step, the collected data is analysed by using statistical tools i.e. SPSS (Statistical Package for Social Science) and AMOS. The results of the structural equation modelling, found that trust, tourist emotion, and Israel risk have a significant relationship with political stability and tourist loyalty. In addition, political stability also acts as a mediator in the relationship between trust, tourist emotion, Israel risk, and tourist loyalty. Although destination image has a significant relationship with tourist loyalty, there is a negative relationship between destination image and political stability. Political stability does not act as a mediator in the relationship between destination image and tourist loyalty. The most important finding is that human behaviour measurement of tourist loyalty entails the focus on tourist emotion as this variable had the top effect towards both variables (political stability and tourist loyalty). Tourism managers should focus on improving the positive image of Jerusalem to increase influx of guests, more revenue, and sustainability because successful t0UIism development is closel related to lower risk at a destination.